STUDI PENGGANTIAN FREON DENGAN CAMPURAN PROPAN DAN BUTAN DALAM SISTEM REFRIJERASI - Pratondo, Toto
The use of freon for refrigerant had been forbidden since 1998 become it had been predicted that freon was responsible for the impact of environment. As the alternative of possibility using hydrocarbon, especially a mixed propane butane as safe materials, has been being studied. The steps of research is started with theoretical consideration to gain reference data, then a laboratory investigation is performed to have measured data needed. The Soave Redlich Kwong equation of state is used to calculate thermodynamic data of freon, propane, normal butane, isobutane and mix of propane-normal butane. By the help of ASPEN PLUS software, it can be shown that the calculation using the SRK-EOS gives good result ( temperature and enthalphy at vapor-liquid phase equilibrium). The experiment was carried out using refrigerant system available in Laboratorium Termodinamika PAU ITB, with refrigeration capacity of 1.79 10.17 kW. This study shown that refrigeration using hydrocarbon that mixed with 60% propane and 40% butane gives 1.46 3.16 coefficient of performance with refrigerant mass flow on 2.51 6.95 kg/s. At the same time heat transfer capacity absorbed by the refrigerant is 767.29 1191.3 kJ/s. Heat transfer capacity (UA) is influenced by refrigerant mass flow circulation either in the condensor or in the evaporator, but for hydrocarbon refrigerant mass flow circulation influence was not seen. The capacity of hydrocarbon refrigerant heat transfer is lower that R-12 refrigerant.